La alfarería de Caspana en relación a la prehistoria tardía de la subárea circumpuneña. - Uribe R., Mauricio (Universidad Católica del Norte, Instituto de Investigaciones Arqueológicas y Museo, 2018)
In this paper we present an actualized vision or the Atacama Desert late pottery (900- 1600 A.D.), using the cumplete vessels of the prehispanic cemetery Los Abuelos de Caspana like a reference sample. Ithave been analyzed, contextualized and compared with the material of other sites of the Rio Loa Basin and the Salar de Atacama. So, we have made a detailed revision that have permited to discusse theregional cultural-historical secuence and to propose a develop process for the circumpunian people of this territorie. In this case, the ceramic suggest a solid cultural unity that probably was constructed by mean of the relations with "frontiers" zones like Tarapaca, Southern Altiplano and Northwestern Argentina territories.